Aproveitamento de resíduo de beneficiamento do caulim na produção de porcelanato cerâmico - Moraes, Márcio Luiz Varela Nogueira de (2007)
Nowadays, industries from all sectors have great concerns over the disposition of the residues generated along the productive process. This is not different in the mineral sector, as this generates great volumes of residues. It was verified that the kaolin improvement industry generates great volumes of residue basically constituted of kaolinite, muscovite mica and quartz, which are basic constitution elements to formularisations of ceramics masses to the production of covering of stoneware tiles type. This happens because the methodology applied to the improvement process is still very rudimentary, what causes a very low yield, only ¼ from all the material volume that enters the improvement process, in the end, is marketable. The disposal of this residue, in a general way, causes a very big negative environmental impact, what has justified the researches efforts aiming to find a rational solution to this problem. In this way, the intention of this present work is the utilization of this residue in the manufacture of products to high quality ceramics covering, stoneware tiles in an industrial scale. For this purpose, the influence of the addition of the residue to a standard ceramics mass used by a ceramics sector company, already established in the market, with the intention of verifying the possibility of use of this residue as the mass complementary raw material and even the possible partial or total substitution of one of the components of the mass for the raw material in evidence will be studied. To the accomplishment of this work, the kaolin improvement residue generated by an industry of exploitation and improvement of kaolin, located in the region of Equador-RN, in the levels 1,2,4,8, 16 and 32% will be added to the standard mass already used for the production of stoneware tiles. The raw materials used, kaolin residue and the standard mass, were characterized through DRX, FRX, DTA, TGA and dilatometry. After the sintering of the bodies of test, tests of water absorption, apparent porosity, post burning linear retraction, apparent specific mass and flexural strength (3 point bending) were realized to determinate the technological properties of these materials. The results show the studied residue can be considered raw material of great potential to the industry of floor and ceramics covering of the stoneware tiles type